2021
DOI: 10.1177/17562848211011953
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of clinical guidelines for antimicrobial management of Clostridioides difficile infection

Abstract: Clostridioides difficile infection (CDI) has been an epidemic for many years. Our biggest challenge in treating CDI is preventing recurrence, which is seen in approximately 25% of patients with initial infection and in 40–60% of those with subsequent episodes. Given the major disease burden of this infection, appropriate data-driven treatment remains essential. Clinical treatment guidelines provide an unbiased critical analysis of the literature, integrating the quality of the available data to make recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Although resistance to antimicrobials recommended by guidelines for the treatment of CDI remains quite rare [ 32 , 33 ], these guidelines have been modified and reshaped over the years, also to address this issue. In particular, the first guidelines (1995–1997) were focused on the administration of vancomycin and metronidazole, while from 2014 to date they also include treatment with fidaxomicin [ 67 ]. Fortunately, most countries in a pan-European study [ 32 ] reported metronidazole, vancomycin and fidaxomicin resistance below 10% (most of them reported 0%), and a species-wide genomic study [ 33 ] could identify pCD-METRO plasmid (conferring metronidazole resistance) in only 15 of > 10,000 strains tested.…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although resistance to antimicrobials recommended by guidelines for the treatment of CDI remains quite rare [ 32 , 33 ], these guidelines have been modified and reshaped over the years, also to address this issue. In particular, the first guidelines (1995–1997) were focused on the administration of vancomycin and metronidazole, while from 2014 to date they also include treatment with fidaxomicin [ 67 ]. Fortunately, most countries in a pan-European study [ 32 ] reported metronidazole, vancomycin and fidaxomicin resistance below 10% (most of them reported 0%), and a species-wide genomic study [ 33 ] could identify pCD-METRO plasmid (conferring metronidazole resistance) in only 15 of > 10,000 strains tested.…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 99%
“…Below, we discuss the antimicrobial resistance mechanisms for medications commonly recommended for the treatment of CDI. Regarding the mechanisms of resistance, C. difficile strains can encode a vanG-type gene cluster ( vanGCd ), conferring resistance to vancomycin, an antimicrobial glycopeptide that inhibits bacterial cell wall biosynthesis [ 67 ]. Specifically, resistance is conferred by the production of an alternative lipid II carrying a D-alanine-D-serine terminus that is seven times less bound by vancomycin than the D-alanine-D-alanine terminus [ 68 ].…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of LBPs stemmed from the concept of FMT, and are defined by the US FDA as a biological product containing live organisms, such as bacteria, that are applicable to the prevention, treatment, or cure of a disease [ 10 ]. The best example of this is the role that microbiota-based LBPs play in the reduction of rCDI [ 11 , 12 ]. The relationship between intestinal microbial diversity in a healthy state, and dysbiosis resulting in rCDI risk, has led to the development of new therapeutic approaches that include LBPs, which have demonstrated efficacy in reducing future CDI recurrences [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment guidelines for management of CDI have changes over the last three decades. Chaar and Feuerstadt 10 review the evolution of clinical guidelines for antimicrobial management of CDI including initial guidelines from the 1990s, a second wave from 2009 up to 2013, and a modern era of treatment guidelines from 2014 to date. Initial guidelines recommended metronidazole as a preferred treatment which changed to vancomycin owing to high failure rates with metronidazole.…”
mentioning
confidence: 99%